Studies on frozen characteristics of individually quick frozen and block frozen mackerel - and Gopakumar, K., Ravindranathan Nair, P., George, C. Thampuran, N. Perigreen, P.A. (Fishery Technology, 2021)
Studies on mackerel (Rastrelliger kanagurta) of medium (4%) and high (11%) lipid contents quick frozen individually (IQF) and as blocks (BF) and stored at -23Â°C showed that block frozen mackerel had higher frozen storage shelf-life than individually quick frozen samples. IQF samples of medium and high lipid contents had shelf-lives of 17 and 20 weeks whereas BF samples of both series had 23 and 24 weeks respectively based on sensory evaluation.